Assessment of Drug-related Queries Received by Clinical Pharmacists in a Rural Community of India - Sarkar, Barun Ranjan (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: This study aimed to assess how clinical pharmacist’s at newly established drug information and patient counseling center responded to different drug information inquiries received in a rural community of India. Method: A prospective unicentric study was conducted from December 2021 to May 2023. Socio-demographic information, how inquiries were received and responded to, types of references used and other aspects were recorded in a specially designed data collection form based on a “modified systemic approach” for a drug information query. Descriptive analysis was carried out using frequencies and percentages and to streamline the reporting outcomes were displayed in tables and figures. Result and Discussion: During the study period, a total of 423 drug information queries were received, majority of queries were through direct walk-ins (50.12%), In written format (33.81%) followed by telephonic communication (12.53%). More than 50% of the queries were from people having graduate qualifications. In our study, the number of queries received (423) were less as compared to other studies and maximum queries were related to side effects and use of drugs. The tertiary sources such as textbooks and internet resources were the most frequently used resources to answer the queries. Conclusion: In this study a strong association between patients and Clinical Pharmacist’s was observed as most of the inquiries were patient-specific. This highlights the growing role Clinical Pharmacist’s which they can play in patient care and towards addressing the drug-related needs of rural India. Furthermore, to encourage the rational use of medicines, it is also necessary to raise awareness about drug information services among general public in rural areas.